2021
DOI: 10.1248/bpb.b21-00245
|View full text |Cite
|
Sign up to set email alerts
|

Dlx5 Represses the Transcriptional Activity of PPARγ

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a master transcription factor in adipocyte differentiation, while distal-less homeobox 5 (Dlx5) is essential for initiating osteoblast differentiation by driving Runt-related transcription factor 2 expression. Considering that adipocytes and osteoblasts share common progenitors, there is a reciprocal correlation between bone and fat formation. However, the mechanism by which Dlx5 controls PPARγ remains unclear. We elucidated that Dlx5 physically binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…BMP-2, a member of the BMP family of growth factors, is primarily distributed in bone tissue and activates the production of bone formation-specific transcription factors by receiving extracellular stimulatory signals from osteoblasts, thus promoting bone formation [ 23 ], whereas Runx2 is a specific transcription factor for bone formation. BMP-2 can promote osteogenesis by activating ERK1/2 and increasing the expression of Runx2 by elevating its phosphorylation level [ 24 ]. RT-PCR and western blotting revealed that BMP-2 and Runx2 proteins and mRNA expression were significantly decreased in the OVX group, indicating the reduced osteogenic potential of rats following OVX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2, a member of the BMP family of growth factors, is primarily distributed in bone tissue and activates the production of bone formation-specific transcription factors by receiving extracellular stimulatory signals from osteoblasts, thus promoting bone formation [ 23 ], whereas Runx2 is a specific transcription factor for bone formation. BMP-2 can promote osteogenesis by activating ERK1/2 and increasing the expression of Runx2 by elevating its phosphorylation level [ 24 ]. RT-PCR and western blotting revealed that BMP-2 and Runx2 proteins and mRNA expression were significantly decreased in the OVX group, indicating the reduced osteogenic potential of rats following OVX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the undesirable determination of MSC cell fate to the adipogenic lineage is regulated by lineage-specific transcription factors such as runt-related transcription factor 2 (RUNX2) and peroxisome proliferator-activated receptor gamma (PPARγ), which causes an imbalance between osteoblast and adipocytes [ 8 , 9 ]. It has been shown that these two key transcription factors that play important roles in MSC differentiation can be regulated by Distal-Less Homeobox 5 (DLX5), which is known as an enhancer of RUNX2 expression and an inhibitor of PPARγ expression [ 10 12 ]. However, few studies have been conducted on how DLX5 expression is regulated during osteoblast differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%